Fulvic acid degradation in Fenton-like system with bimetallic magnetic carbon aerogel Cu-Fe@CS as catalyst: Response surface optimization, kinetic and mechanism. (15th March 2022) - Qin, Xia; Wang, Ziyuan; Guo, Chengrui; Guo, Rui; Lv, Yue; Li, Mingran
Abstract: In this study, Cu-Fe bimetallic magnetic chitosan carbon aerogel catalyst (Cu-Fe@CS) was prepared by the sol-gel method to degrade Fulvic acid (FA) in Fenton-like system. Degradation experiment results showed bimetallic catalyst Cu-Fe@CS can degrade more FA than monometallic catalysts (Cu@CS and Fe@CS) due to the synergistic effect between the copper and iron. Plackett Buiman (PB) design showed that pH and temperature exhibited significant influence on FA degradation. The significant factors were optimized by Central Composite Design (CCD), the results revealed that the maximum FA removal reached 96.59% under the conditions of pH 4.07 and temperature 93.77 °C, the corresponding TOC removal reached 77.7%. The kinetic analysis implied that the reaction followed pseudo-first order kinetic with correlation coefficient (R 2 ) = 0.9939. The Arrhenius fitting analysis revealed that Cu–Fe@CS had a lower activation energy (Ea) than Cu@CS and Fe@CS, meaning that reaction was easier to occur in Fenten-like system with Cu–Fe@CS. Catalyst still remained the higher FA and TOC removals of 96.28% and 77.33% after six runs, respectively. The FA removal was reduced by 65.53% with 12 mmol tertiary butanol (TBA) as scavenger, indicating that OH played an important role in FA degradation. Finally, the catalytic degradation mechanism was proposed. Graphical abstract: Image 1 Highlights: The optimal FA degradation condition was optimized using PB and RSM. The catalyst of Cu–Fe@CS has lower activation energy to FA degradation than Cu@CS and Fe@CS. The catalyst of Cu–Fe@CS can be recovered by external magnetic field.